The role of psychological ownership in consumer happiness. Issue 6 (15th June 2020) - Li, Dan; Atkinson, Lucy
Abstract : Purpose: This paper aims to examine the effect of psychological ownership on consumer happiness, which is mediated through basic psychological needs satisfaction. Design/methodology/approach: Data were collected by means of two online experiments. Study 1 tested and validated the hypotheses by examining post-consumption on a sample of 252 college students. Study 2 investigated the impact of psychological ownership in a pre-consumption scenario. Findings: The results show that consumers feel happier when they have a higher psychological ownership over an item after consumption. Furthermore, consumers anticipate greater happiness from a product before consumption due to increased psychological ownership through customization. This effect is mediated by the satisfaction of basic psychological needs. Practical implications: The study will help marketers make their products or services as a better candidate for the target of psychological ownership through user experience design. Furthermore, the study encourages new business and marketing models, such as the sharing economy, that exploit the effect of psychological ownership. Originality/value: The core contribution of this study is that it extends self-determination theory by distinguishing the effect of legal and psychological ownership on consumer happiness. It provides a better understanding of the psychological mechanism behind happiness.